Comparison of RMI 3 and RMI 4 in pre-operative evaluation of ovarian masses - Bahadur, Badugu Rao; Koneru, Gangadhara Rao; Kodey, Prabha Devi; Melam, Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To differentiate ovarian mass as benign or malignant could change clinical approach. Finding a screening and diagnostic method for ovarian cancer is challenging due to high mortality and insidious symptoms. Risk malignancy index (RMI) has the advantage of rapid and exact triage of patients with ovarian mass. Methods: Prospective study carried for 2 years at NRI Medical College and General Hospital, Chinakakani, Mangalagiri, Andhra Pradesh, India. 79 patients with ovarian mass were investigated and risk malignancy index (RMI-3 and RMI-4) calculated. Final confirmation was done based on histopathological report. Sensitivity, specificity, positive predictive value and negative predictive value were calculated for RMI 3 and RMI 4 taking histopathology as control and comparison was done. Results: (n=79); 50 (63.29%) cases were benign and 29 (36.70%) were malignant based on histopathology. RMI 4 is more sensitive (68.96%) than RMI 3 (62.06%), but RMI 3 is more specific (94%) than RMI 4 (92%).The positive predictive value of RMI-3 and RMI-4 were 85.71% and 83.33% respectively. The negative predictive value for RMI-4 and RMI-3 were 83.63% and 81.03% respectively. Conclusions: With increasing age, chance of malignancy increases. RMI 4 was more sensitive than RMI-3, however less specific than RMI 3 in differentiating benign and malignant tumors. The positive predictive value is slightly more for RMI 3, than RMI 4. Negative predictive value is slightly more for RMI 4, than RMI 3.